Evolution of ozone depletion on Antarctic and Sub-Antarctic regions (1979-2012) - Diaz, Susana Beatriz; Paladini, Alejandro Alberto; Deferrari, Guillermo Alejandro; Vrsalovic, Jazmin (SPIE Proceedings, First International Conference on Remote Sensing and Geoinformation of the Environment (RSCy2013))
At the middle eighties, strong stratospheric ozone depletion during spring was discovered over Antarctica. Since then, the scientific community has put large efforts in performing studies directed to evaluate the magnitude and consequences of this depletion and to take the necessary measures to revert the situation to the scenarios before 1970. In 1987, the Montreal Protocol established a list of ozone depleting products and faced out policies. As consequence of these restrictions on ozone depleting substances, the ozone layer should start to recover in the 21st century. In order to study the evolution of the Antarctic ozone depletion, we analyzed the ozone hole area and mass deficit and seasonal total ozone column (TOC) minimum. We also performed a seasonal and bi-monthly analysis for TOC time series (1979-2012), at twenty Antarctic and Sub-Antarctic stations. The number of days inside the vortex (TOC below 220DU) per season (September-December) and for September-October and November-December were analyzed, fitting the time series with a second degree polynomial According to this study, ozone hole area would have peaked between 2001 and 2002 (R=0.91, p<0.01), while the minimum TOC would have occurred between 2000 and 2001(R=0.91, p<0.01). Mass deficit is only provided since 2005 and it showed a decrease since then, although ot statistically significant as consequence of the short time series. From the 20 analyzed stations, 80% showed that the number of days per season inside the vortex peaked between 2000 and 2003 and for 55% of the stations the number of days inside the vortex for September-October peaked between 1999 and 2004. Fil: Diaz, Susana Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Paladini, Alejandro Alberto. Consejo Nacional de Investigaciones Científicas y ...